2021
DOI: 10.1111/joa.13462
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of age at onset of linear enamel hypoplasia. New calculation tool, description and comparison of current methods

Abstract: Enamel Hypoplasia (EH) is known to be a useful indicator for wide range of detrimental factors in early childhood in past populations, such as nutritional disturbances, mechanical trauma, disease, metabolic, and/or genetic disorders. EH may be divided into three categories: pits, grooves, and lines, where the last two are referred to as “Linear Enamel Hypoplasia” (LEH). The regularity of enamel formation allows retrospective determination of the age of LEH formation. The current article reviews and compares th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…Linear enamel hypoplasia (LEH) is a good indicator of metabolic stress in childhood (Littleton & Townsend, 2005;Novak et al, 2009;Dąbrowski et al, 2021). In the Pula sample, LEH is present in almost all examined incisors and canines, representing a very high prevalence of enamel defects in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear enamel hypoplasia (LEH) is a good indicator of metabolic stress in childhood (Littleton & Townsend, 2005;Novak et al, 2009;Dąbrowski et al, 2021). In the Pula sample, LEH is present in almost all examined incisors and canines, representing a very high prevalence of enamel defects in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This high frequency is probably not related to the small sample size, as the defects were consistently present in every individual. High rates of LEH were linked to the increased physiological stress in the population because of disease, nutritional deficiencies (Littleton & Townsend, 2005;Dąbrowski et al, 2021), lifestyle based on agriculture, increase in population (Cohen & Armelagos, 1984) and population aggregation (Ham et al, 2020). This stress could result from weaning when children transition from consuming breast milk to other foods that contain microorganisms that can cause digestive distress, reduce appetite, and cause nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…It was scored as present in cases where at least one tooth manifested a reduction in the normal thickness of enamel, usually in the form of horizontal grooves (Riga et al, 2014;Ritzman et al, 2008). In bioarchaeology, linear enamel hypoplasia is considered indicative of metabolic stress during childhood, as the physiological disruptions that cause it only affect the portion of the crown that is in the process of forming (Dąbrowski et al, 2021;Guatelli-Steinberg, 2004;Ritzman et al, 2008). Although the precise etiology of linear enamel hypoplasia is not well understood yet, it is most commonly associated with protein and vitamin deficiencies, childhood disease and injuries (Armelagos et al, 2009;Nunn, 2001;King et al, 2002;Tomczyk et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The most frequently observed surface hypoplastic defect in bioarcheological studies is linear enamel hypoplasia (LEH), transverse lines, or pits on the lateral enamel surface (Hillson, 2005). However, LEH-based studies often provide only a crude chronology of physiological stress experiences in comparison to observations of internal incremental enamel structures (Armelagos et al, 2009;Blakey, 1998;Boldsen, 2007;Dąbrowski et al, 2021;Goodman & Rose, 1990;Miszkiewicz, 2015). There has been some discussion as to whether ameloblasts are more or less sensitive to stressors at different periods of their secretory lifespan, and it has been suggested that this may influence the severity or intensity of ameloblast dysfunction (Aris & Street, 2021;Dean et al, 2020;FitzGerald et al, 2006;FitzGerald & Saunders, 2005;Kierdorf et al, 2021;Witzel et al, 2008).…”
Section: Physiological Stress and Enamel Growth And Disruptionmentioning
confidence: 99%